PROGRAM INTERVENSI DALAM UPAYA PENURUNAN KASUS BARU TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS TELUKNAGA - Hana Adytia; Edwin Destra; Nada Fadila Kinantya (Yayasan Pendidikan Medika Indonesia, 2022)
Introduction: According to WHO in 2020, tuberculosis (TB) is the 13th leading cause of death in the world. Indonesia ranks as the third highest country for new TB cases and has reached 845,000 cases. The number of new cases in Indonesia is still increasing and there are still treatment discontinuation and undetected cases. Objective: To reduce new TB cases in Teluknaga Health Center. Method: This research uses pre-test and post-test for assessment with interventions carried out in the form of counseling and demonstration of cough etiquette to increase public knowledge. Sample was selected using non-random consecutive sampling. Independent variable in this study is the intervention carried out to increase public knowledge. Dependent variable in this study is change in knowledge. Result: 30 Respondents experienced an increase in knowledge in 10 selected aspects which are considered as indicators of knowledge. Conclusion: Interventions were carried out in the form of counseling about tuberculosis and cough etiquette, with cough demonstrations have succeeded l in increasing public knowledge about pulmonary TB. It is hoped that there will be changes in people's attitudes and behavior in preventing the spread of tuberculosis infection in the community.